PENGARUH STRUKTUR KEPEMILIKAN DAN ESG TERHADAP EFISIENSI MODAL INTELEKTUAL - Santoso, Karina; Handoko, Jesica (Jurnal Aplikasi Akuntansi, 2024)
The progress of the current era of globalization is slowly changing the company's view from a labor-based business to a knowledge-based business. The knowledge-based business is based on the ability and proficiency of the company's individuals. This is what makes the company focus on increasing intellectual capital. Several factors, such as ownership structure and Environmental, Social and Governance (ESG) activities, are thought to influence the efficiency of intellectual capital because both reflect the entity's intellectual capital. This research aims to determine the effect of ownership structure (managerial ownership, institutional ownership, foreign ownership, government ownership) and ESG activities on the intellectual capital efficiency of non-financial sector companies listed on IDX in 2018-2022. The purposive sampling technique was used and resulted in 78 companies that met the criteria. The research was conducted using multiple linear regression analysis via SPSS 23. The results of the research show that managerial ownership does not affect intellectual capital efficiency. The research results also reveal that institutional ownership and ESG activities have a positive effect on intellectual capital efficiency. On the other hand, foreign ownership and government ownership have a negative effect on intellectual capital efficiency. The results of the research provide an overview for companies regarding the influence of ESG activities on company reputation, contribution, and quality. On the other hand, ownership variables can provide an overview of the company regarding the influence of share ownership on company decisions.